Physiological potential of genipap seed and in vitro growth of accessions under saline stress - Nascimento Cardoso, Milena; Albuquerque Resende Oliveira, Leila; Naiana Ribeiro Soares, Adrielle; da Silva Ledo, Ana; Veruska Cruz da Silva, Ana (Pesquisa Agropecuaria Brasileira, 2026)
The objective of this work was to evaluate the effect of saline stress on the physiological potential of seed and on in vitro growth of three genipap accessions. Seed of accessions NB (Núcleo Bandeirante, DF), SA (Sabinópolis, MG) and CRA (Cruz das Almas, BA) were subjected to NaCl concentrations (at 0, 25, 50, 75, and 100 mmol L-1) for 40 days. The germination was evaluated until seedling formation. Every 72 hours, embryonic axes of seed subjected to saline concentrations were extracted, to determine the enzyme activity of superoxide dismutase (SOD), catalase (CAT), and ascorbate peroxidase (APX). To evaluate the initial growth, explants of the accessions were inoculated in MS medium added with the same NaCl concentrations and, at 30, 60, and 90 days, proline was quantified. The concentration at 50 mmol L-1 NaCl increased the SOD and APX activity up to 288 hours of exposure to saline stress. The SA accession showed the greatest tolerance to saline stress, with proline increase at 30, 60 and 90 days. Saline stress affects the genipap germination and its initial in vitro growth with varying degrees of tolerance among accessions, for which SA showed the highest degree.
Keywords: Genipa americana; antioxidant enzymes; Brazilian fruit; proline